Implicit and Explicit Learning of a Sequential Postural Weight-Shifting Task in Young and Older Adults - Caljouw, Simone R.; Veldkamp, Renee; Lamoth, Claudine J. C. (Frontiers in Psychology, 2016)
Sequence-specific postural motor learning in a target-directed weight-shifting task in twelve older and twelve young participants was assessed. In the implicit sequence learning condition participants performed a concurrent spatial cognitive task and in the two explicit conditions participants were required to discover the sequence order either with or without the concurrent cognitive task. Participants moved a cursor on the screen from the center location to one of the target locations projected in a semi-circle and back by shifting their centre of pressure on force plates. During the training the targets appeared in a simple fixed 5-target sequence. Plan-based control (i.e. direction of the CoP displacement in the first part of the target-directed movement) improved by anticipating the sequence order in the implicit condition but not in the explicit dual task condition. Only the young participants were able to use the explicit knowledge of the sequence structure to improve the directional error as indicated by a significant decrease in directional error over practice and an increase in directional error with sequence removal in the explicit single task condition. Time spent in the second part of the movement trajectory to stabilize the cursor on the target location improved over training in both the implicit and explicit sequence learning conditions, for both age groups. These results might indicate that an implicit motor learning method, which holds back explicit awareness of task relevant features, may be desirable for improving plan-based motor control in older adults.